BRIDGING THE INFORMATION AND DIGITAL DIVIDE AT HIGHER EDUCATIONAL INSTITUTIONS - Alla M. Kolomiiets; Anatolii O. Klymenko (Інформаційні технології і засоби навчання, 2014)
The article deals with the notion of information and digital divide on the grounds of the world processes of the information society establishment. This paper presents a research of the level of informatization of the main spheres of life activity of citizens of foreign countries, and the analysis of the experience of the leading countries in organization and implementation of a complex of measures, aimed at crossing the digital divide. Also, there have been outlined the peculiarities and problems of the development of higher education in Ukraine in the context of information and digital inequality. On the basis of the analysis of scientific literature and personal professional experience, the ways of the solution of the problem of teacher’s selection of the adequate and the most effective pedagogical technologies, forms and methods of study in the process of overcoming the information and digital divide at higher educational institutions have been determined in this article.